An effort to increase english teachers' teaching competency through ICT-based innovative learning media - Rokhayani, Atik; Shofiyuddin, Muhammad; Latifah, Noor (Galuh International Journal of Community Service and Development, 2025)
Various activities and programs have been implemented to develop English education, especially in Kudus, Central Java. However, there are still several urgent problems that need to be resolved, namely the teaching competence of MA English MGMP teachers in Kudus, which needs to be improved through the provision of assistance and the implementation of the English Key learning model and ICT media. This community service program has four areas of focus, namely learning management, tenses learning model, human resources and supporting competencies. The method used is provision and mentoring. The solution will be implemented through the following methods and stages: 1. Socialization and Deliberation, 2. Training and Provision, 3. Implementation of competency in teaching tenses and ICT Media, 4. Mentoring and Evaluation, 5. Program Sustainability. In implementing this Community Service Program, the science and technology used by the implementing team is the implementation of the Wrench and TOEFL Approach which are provided and used in carrying out provision and mentoring to partners. The wrench and TOEFL approach were chosen because of their effectiveness, systematicity and ease of learning even for beginners, considering that implementers have limited time to achieve maximum results.